Desenvolvimento de uma aplicação de rede social corporativa - Abreu, Lucas Henrique de (2017)
The number of companies in Brazil is increasing, as well as the volume of data that these produce and use. The companies have the need of internal communication, exchange of files, dissemination of knowledge, scheduling of meetings and events, reservation of rooms and materials, among others, however, to meet their demands, they end up using distinct solutions or basically using their mail server for all of these activities. Therefore, understanding that organizations seek better communication among their employees and have the need to centralize information, files and workflow, this project was develop a software that has features related to the management of user profile, timeline, chat, event scheduling, and group creation. The application meets all the needs presented and is developed as a web application based on a social network, such as Facebook, because the widespread use of social networks and familiarization of the use of such networks by people facilitates the adaptation of this system. The application in this format provides a very broad vision to the Human Resources Manager from the manipulation of the data produced by the users and employees of the company. This data can be presented in the dashboard format, with preferences and assessment of the level of employee satisfaction with the company and the workplace. In addition, the application provides data to the administrator that enables an analysis of each user and groups, aiming at improving communication and agility in the workflow.